2022
DOI: 10.3389/fnins.2022.839874
|View full text |Cite
|
Sign up to set email alerts
|

Low Heart Rate Variability Predicts Poor Overall Survival of Lung Cancer Patients With Brain Metastases

Abstract: BackgroundThe aim of this prospective study was to evaluate the association between heart rate variability (HRV) and overall survival of lung cancer patients with brain metastases (LCBM).MethodsFifty-six LCBM patients were enrolled in this study. Five-minute electrocardiograms were collected before the time to first brain radiotherapy. HRV was analyzed quantitatively by using the time domain parameters, i.e., the standard deviation of all normal-normal intervals (SDNN) and the root mean square of successive di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“… De Couck et al (2016) found that SDNN can significantly predict the overall survival in patients with advanced pancreatic cancer. In addition, our previous study showed that there is an independent association between RMSSD and overall survival in LC patients with brain metastasis ( Wu et al, 2022 ). Although most previous studies showed that vagal activity based on linear HRV has a prognostic effect on cancer patients, a few studies found that the change in linear HRV is not an appropriate marker for predicting overall survival in advanced NSCLC patients.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“… De Couck et al (2016) found that SDNN can significantly predict the overall survival in patients with advanced pancreatic cancer. In addition, our previous study showed that there is an independent association between RMSSD and overall survival in LC patients with brain metastasis ( Wu et al, 2022 ). Although most previous studies showed that vagal activity based on linear HRV has a prognostic effect on cancer patients, a few studies found that the change in linear HRV is not an appropriate marker for predicting overall survival in advanced NSCLC patients.…”
Section: Discussionmentioning
confidence: 95%
“…Time domain analysis is the simplest and easiest method to study HRV and can provide relatively clear physiological information, which is easily accepted by clinicians. The published literature suggests that SDNN and RMSSD are significantly associated with the overall survival of patients with advanced malignant tumors ( Wang Y. M. et al, 2013 ; De Couck et al, 2016 ; Wu et al, 2022 ). For example, Wang Y. M. et al (2013) showed that SDNN is an independent prognostic factor for the overall survival of patients with brain metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… Wang et al (2013 , 2021) showed a significant correlation between the time-domain index SDNN and the survival time of BM patients, and SDNN was an independent prognostic factor for patients with BM. Wu et al (2022) first explored the association between HRV time domain indexes (SDNN and RMSSD) and the survival of LCBM patients. The results showed that RMSSD, the time domain index, can be used as an independent prognostic factor for the survival of patients with LCBM.…”
Section: Discussionmentioning
confidence: 99%
“…The methods for quantitative analysis of HRV are mainly based on linear methods in the time and frequency domains and nonlinear methods. Existing studies on the relationship between the time- and frequency-domain parameters of HRV and the prognosis of many kinds of malignant tumors, such as liver cancer ( Chiang et al, 2010 ), pancreatic cancer ( De Couck et al, 2016 ), BM ( Wang et al, 2013 ; Wang et al, 2021 ), colorectal cancer ( Strous et al, 2020 ) and LCBM ( Wu et al, 2022 ), have shown that a low level of linear HRV is associated with poor prognosis of cancer patients, which is of great significance for the formulation of treatment strategies for cancer patients.…”
Section: Introductionmentioning
confidence: 99%